The Cytoprotective Enzyme Heme Oxygenase-1 Suppresses Pseudorabies Virus Replication in vitro - Zhang, Angke; Wan, Bo; Jiang, Dawei; Wu, Yanan; Ji, Pengchao; Du, Yongkun; Zhang, Gaiping (Frontiers in Microbiology, 2020)
Pseudorabies virus (PRV) infection brings about great economic losses to the swine industry worldwide, as there are currently no effective therapeutic agents or vaccines against this disease, and mutations in endemic wild virulent PRV strains result in immune failure of traditional vaccines. Heme oxygenase-1 (HO-1) catalyzes the conversion of heme into biliverdin (BV), iron and carbon monoxide (CO), all of which have been demonstrated to protect cells from various stressors. However, the role of HO-1 in PRV replication remains unknown. Thus, the present study aimed to investigate the effect of HO-1 on PRV replication and determine its underlying molecular mechanisms. The results demonstrated that induction of HO-1 via cobalt-protoporphyrin (CoPP) markedly suppressed PRV replication, while HO-1 specific small interfering RNA or inhibitor zinc-protoporphyrin partially reversed the inhibitory effect of CoPP on PRV replication. Furthermore, overexpression of HO-1 notably inhibited PRV replication, while knockdown of endogenous HO-1 expression promoted PRV replication. Mechanism analyses indicated that the HO-1 downstream metabolites, CO and BV/BR partially mediated the virus suppressive effect of HO-1. Taken together, the results of the present study suggest that HO-1 may be developed as a novel endogenous antiviral factor against PRV, and the HO-1/BV/CO system may constitute a unique antiviral protection network during PRV infection and interaction with host cells.